Robot-assisted Pelvic Reconstruction Using Rectus Abdominis Flap: Efficiency Evaluation of Adding a Third Surgeon - Matthew W. Kelecy, MD; Noama Iftekhar, MD; Brett Allen, MD; Edozie Ezeanolue, BS; Richard C. Baynosa, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The open rectus abdominis flap has long been a versatile workhorse in pelvic reconstruction. In an effort to reduce morbidity of open approach, robotic harvest techniques have been developed. Our institution previously published a retrospective study that compared outcomes between the robotic and open approaches between 2014 and 2019. Since then, our technique has evolved to include the addition of a general surgeon for simultaneous harvest site closure and flap insetting. Methods:. This is an institutional review board–approved single-institution retrospective review of patients who underwent robotic rectus harvest using Da Vinci surgical system for perineal reconstruction between 2018 and June 2023. The dataset was stratified into patients who underwent 3-surgeon reconstruction versus 2-surgeon reconstruction. Data collected included demographics, risk factors, perioperative information, and postoperative outcomes. Results:. In total, 21 patients underwent robotic rectus repair from 2018 to 2023 with operations occurring at 3 different hospitals. Of those patients 7 were excluded, resulting in 14 patients included for evaluation: 8 patients who underwent 3-surgeon operation and 6 in the 2-surgeon cohort. We found no difference in total operative time (508.1 versus 506.8, P = 0.48), total robotic console time (445.7 versus 424.0, P = 0.46), hospital length of stay (11.4 versus 8.0, P = 0.27), or overall complication rate (0.75 versus 0.83, P = 0.36). Conclusions:. Although this is a small study, the data suggest that plastic surgeons trained in robotic techniques are well-equipped to perform the harvest, mesh repair, and flap inset without the addition of a general surgeon.